The effect of handling children anxiety with modelling techniques to changes in pulse rate in dental and oral care: Pengaruh penanganan kecemasan anak dengan teknik pemodelan terhadap perubahan denyut nadi pada perawatan gigi dan mulut - Sherly Horax; Eri Hendra Jubhari; Sustia Sri Rizki (Makassar Dental Journal, 2021)
Background: Oral and dental care in children causes anxiety and fear so that children become non-cooperative, resulting in suboptimal care provided by dentists so that anxiety management is needed. One form of handling anxiety is a modelling tech-nique which has a psychological principle that by studying the environment changes in behavior occur. Objective: To determine the effect of handling children's anxiety by using modelling techniques on changes in pulse rates in dental and oral care. Me-thods: Analytical observational research using cross sectional method and purposive sampling technique was conducted at the Pediatric Dentistry at Dental Hospital of Hasanuddin University. The samples were children aged 6-12 years who came for the first time to the clinic. The level of anxiety is measured using objective parameters, namely the measurement of the radial pulse before and after three types of modelling; dental modelling, games, and modelling videos. Data were analyzed using the Kol-mogorov Smirnov test. Results: The statistical test resulted in a value of p = 0.000 (<0.05) which showed a significant effect of treating children's anxiety using modeling techniques on pulse rate. Conclusion: The modelling technique is effective in redu-cing children's anxiety due to dental treatment.